PERBANDINGAN METODE PEMASARAN TRADISIONAL DAN MODERN: IMPLIKASI UNTUK BISNIS - Hendrik Kuasa Sihura (Universitas Nias Raya, 2026)
This study aims to analyze the differences in characteristics, advantages, and limitations between traditional and modern marketing methods, as well as to identify their implications for the formulation of effective business strategies. The research employs a literature review method with a qualitative analytical approach. Data were collected from various scholarly sources, including journals, books, and relevant academic articles, in order to provide a comprehensive theoretical foundation. The findings indicate that modern digital-based marketing offers several advantages, such as broader market reach, more targeted segmentation capabilities, real-time two-way interaction, cost efficiency, and easier performance evaluation through data analytics. In contrast, traditional marketing continues to play a significant role in building emotional connections, enhancing brand credibility, and reaching consumers in specific regions or segments that have not been fully exposed to digital technology. These findings suggest that each method holds complementary strategic value. The study underscores that the synergistic integration of traditional and modern marketing approaches can create more adaptive and competitive strategies. Therefore, business practitioners should align their strategic choices with target market characteristics, organizational objectives, and technological developments to achieve sustainable competitive advantage.